Obstructive Sleep Apnea Is Treatable With Continuous Positive Airway Pressure in People With Schizophrenia and Other Psychotic Disorders. (28th September 2021) - Giles, Jamilla J; Ling, Ivan; McArdle, Nigel; Bucks, Romola S; Cadby, Gemma; Singh, Bhajan; Morgan, Vera A; Gabriel, Laura; Waters, Flavie
Abstract: Obstructive sleep apnea (OSA) is a highly prevalent condition in people living with schizophrenia or other psychotic disorder. Its treatment with continuous positive airway pressure therapy (CPAP) can dramatically improve daytime and physical health function. People with a psychotic disorder, however, are rarely diagnosed and treated and there are no large-scale studies showing evidence of successful treatment with CPAP. Using a retrospective case-control study approach ( N = 554), we examined adherence to and effectiveness of a CPAP trial in individuals with comorbid psychotic disorder and OSA (psychosis group, n = 165) referred for a CPAP trial at the West Australian Sleep Disorders Research Institute. Given that antipsychotic medication is an important confounder, we included a psychiatric (non-psychosis) comparison group taking antipsychotic medication (antipsychotic group, n = 82), as well as a nonpsychiatric control group (OSA control group, n = 307) also diagnosed with OSA and referred for CPAP. Variables included OSA symptom response, CPAP engagement, and usage at 3 months. The Psychosis group had the most severe OSA at baseline and they attended fewer clinic appointments overall. However, there were no other group differences either in CPAP adherence or treatment response. CPAP was equally effective in normalizing OSA symptoms and daytime sleepiness in all groups. CPAP usage was longer per night in the Psychosis and Antipsychotic groups, perhaps suggesting a role of sedation from antipsychotic medications. In conclusion, OSA is treatable and CPAP feasible in people with severe mental illness and antipsychotic medications are not a barrier to treatment response.